INVENTARISASI DAN KEBERADAAN JENIS POHON DI SEKITAR TLOGO NIRMOLO DAN TLOGO MUNCAR TAMAN WISATA KALIURANG - , TULIS DYAH NILAMSARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Nirmolo and Muncar Lake, or so called Tlogo Nirmolo and Tlogo Muncar, are part of Kaliurang Tourism Park. There are numerous kinds of composing trees which has not been on data until today, so that a research on trees inventory is needed. This research is begun with a survey to find out the actual condition in the field and the current vegetation. Furthermore,data collection was conducted through 100% inventory. Next, the counting step, listing down every type and total number of trees. The research finds out that there are 44 types on 30 families and 119 individualis contains of 95 individualis at tree level, and 24 others at pole level. From the 44 types, the planted plants are 18 types and the rest of 26 grow wildly.